2013
DOI: 10.1101/gad.227249.113
|View full text |Cite
|
Sign up to set email alerts
|

The p53–Mdm2 feedback loop protects against DNA damage by inhibiting p53 activity but is dispensable for p53 stability, development, and longevity

Abstract: The p53-Mdm2 feedback loop is perceived to be critical for regulating stress-induced p53 activity and levels. However, this has never been tested in vivo. Using a genetically engineered mouse with mutated p53 response elements in the Mdm2 P2 promoter, we show that feedback loop-deficient Mdm2 P2/P2 mice are viable and aphenotypic and age normally. p53 degradation kinetics after DNA damage in radiosensitive tissues remains similar to wild-type controls. Nonetheless, DNA damage response is elevated in Mdm2 P2/P2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
92
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 69 publications
(97 citation statements)
references
References 46 publications
(72 reference statements)
5
92
0
Order By: Relevance
“…Using the mouse model in which the p53-Mdm2 feedback loop is disrupted, we observed that DNA damage-stabilized p53 degraded just like in wild-type tissues, but the rate of degradation was slightly delayed. This suggests that other proteins cooperate with Mdm2 in degradation of p53 after stress (Pant et al 2013;Pant and Lozano 2014). Unfortunately, ubiquitination was not assayed in tissues from these mice due to technical challenges.…”
Section: Mdm2 Is Not Alonementioning
confidence: 99%
See 2 more Smart Citations
“…Using the mouse model in which the p53-Mdm2 feedback loop is disrupted, we observed that DNA damage-stabilized p53 degraded just like in wild-type tissues, but the rate of degradation was slightly delayed. This suggests that other proteins cooperate with Mdm2 in degradation of p53 after stress (Pant et al 2013;Pant and Lozano 2014). Unfortunately, ubiquitination was not assayed in tissues from these mice due to technical challenges.…”
Section: Mdm2 Is Not Alonementioning
confidence: 99%
“…We recently tested this paradigm in a mouse model in which the feedback loop was disrupted due to mutations in the p53-binding sites in the Mdm2 P2 promoter. While mice lacking the p53-binding sequences in the P2 promoter are normal, they exhibit hematopoietic defects and die after exposure to low-dose ionizing radiation (Pant et al 2013;Pant and Lozano 2014).…”
Section: The Mdm2 E3 Ligasementioning
confidence: 99%
See 1 more Smart Citation
“…Under normal physiological conditions, the anti-proliferative functions of p53 are strictly inhibited, mainly by the actions of an E3 ubiquitin ligase, MDM2, which mediates p53 ubiquitination and degradation. The MDM2 gene is also a p53 target, which forms a feedback loop that restrains p53 activity (Pant et al 2013). The negative regulation of p53 by MDM2 has been genetically confirmed, as the early embryonic lethality caused by deletion of the MDM2 gene can be rescued by p53 deletion (Montes de Oca Luna et al 1995).…”
mentioning
confidence: 93%
“…In most of human cancers (Ozaki and Nakagawara, 2011), p53's functions are compromised either by loss-of-function mutations or by the defects that occur in the other components of the pathway. Under normal conditions, the p53 is strictly inhibited mainly by an E3 ubiquitin ligase, murine double minute 2 (MDM2), which inhibits p53 transcription activity and also mediates p53 ubiquitination and degradation (Pant et al, 2013). MDM2 is the best characterized negative regulator of p53.…”
mentioning
confidence: 99%